Performance Analysis of 4x4 MIMO and 8x8 MIMO Antena Implementation of Private 5G Networks in Industrial Area - Wulandari, Asri; Supriyanto, Toto; Hasna, Akita; N, Raviadin N; Hikmaturokhman, Alfin (Universitas Medan Area, 2024)
Private 5G represents a promising wireless network technology that offers a wide range of opportunities for mobile operators. It enables them to meet the increasing data demands of their customers and provide enhanced capacities and user experiences. However, before deploying Private 5G, it's crucial to prepare the foundation properly, especially when choosing the right antena and Radio Frequency (RF) band. This research project focuses on evaluating the implementation of 4x4 MIMO and 8x8 MIMO antenas in the Greater Jakarta industrial area, covering a 35 km2 area, operating at a frequency of 2300 MHz with a 40 MHz bandwidth. The study involved data rate measurements and determined the number of required sites based on different modulation schemes. The findings revealed that using an 8x8 MIMO antena resulted in a data rate twice as high as that achieved with a 4x4 MIMO antena and required only a quarter of the sites. Additionally, simulation results demonstrated that the 8x8 MIMO antena provided better SS-RSRP and SS-SINR values compared to the 4x4 MIMO antena, with values of -91.51 dBm and 8.52 dB